Effects from changes in financial standards over corporate taxation - Belaunde Plenge, Walther (2018)
The present paper will analyze the influence that financial standards on the determination of taxable income and, hence, how much instability should cause its modification on corporate taxation.For that purpose, it will show the influence of accounting on corporate taxation determination. Also, it will analyze the legal nature of international financial standards, and its use as legal source in income taxation.